Spontaneous Platinum Deposition on Polyaniline Films with Trapped Carbon Nanotubes - Bavio, Marcela Alejandra (2009)
A polyaniline film (PANI) with incorporated carbon nanotubes (CNTs) was used as substrate to prepare com-posite platinum electrodes. The polymeric film was grown electrochemically on Nichrome and gold wires from the mo-nomer acid solution with suspended carbon nanotubes. Later, Pt catalytic particles were distributed onto the film by spon-taneous deposition varying the deposition time. The results show that the codeposited CNTs significantly influence notonly the amount but also the dispersion of the Pt particles. Methanol oxidation was chosen as model reaction to test thecatalytic properties of the Pt composites. It was found that those with carbon nanotubes show better catalytic performance.